2016
DOI: 10.1111/acel.12484
|View full text |Cite
|
Sign up to set email alerts
|

Secreted microvesicular miR-31 inhibits osteogenic differentiation of mesenchymal stem cells

Abstract: SummaryDamage to cells and tissues is one of the driving forces of aging and age‐related diseases. Various repair systems are in place to counteract this functional decline. In particular, the property of adult stem cells to self‐renew and differentiate is essential for tissue homeostasis and regeneration. However, their functionality declines with age (Rando, 2006). One organ that is notably affected by the reduced differentiation capacity of stem cells with age is the skeleton. Here, we found that circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
141
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(143 citation statements)
references
References 39 publications
2
141
0
Order By: Relevance
“…It has been reported that miR‐31a‐5p negatively regulates skeletogenesis and osteogenesis (Deng, Wu et al., 2013; Jin et al., 2016; Stepicheva, & Song, 2015; Weilner et al., 2016). Previous studies also demonstrated that decreased stemness and increased senescence are the primary causes of declines in osteogenic differentiation of BMSCs (Fehrer, & Lepperdinger, 2005; Zhou et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR‐31a‐5p negatively regulates skeletogenesis and osteogenesis (Deng, Wu et al., 2013; Jin et al., 2016; Stepicheva, & Song, 2015; Weilner et al., 2016). Previous studies also demonstrated that decreased stemness and increased senescence are the primary causes of declines in osteogenic differentiation of BMSCs (Fehrer, & Lepperdinger, 2005; Zhou et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study is that miRNA expression levels of miR-188-3p, miR-382-3p, and miR-550a-5p in hASCs are endogenously very low, and that we could not observe any functional effects on osteogenic and adipogenic differentiation, following miR-knockdown of these three miRNAs, although we used a robust and well-working miRNA knockdown protocol including positive controls. (54) In summary, identifying and evaluating patients at increased risk for diabetes-related or osteoporosis-related fragility fractures is critical to disease prevention and management. Our results suggest that circulating miRNAs are indicative of fragility fractures in T2D and in osteoporotic women and that generating comprehensive sets of highly discriminatory miRNA-signatures can help identifying novel and biologically promising miRNAs which can be then subjected to further in vitro testing.…”
Section: Discussionmentioning
confidence: 99%
“…For osteogenic differentiation, alkaline phosphatase enzyme activity (ALP) and extent of mineralization via Alizarin red staining were measured as early and late markers of osteogenesis using standard methodology. (53,54) Because both assays were not normalized by cell number, we measured RUNX2 and ALP mRNA levels normalized by GAPDH in miR-transfected hASCs 6 days after osteogenic induction as additional, cell-number corrected markers of osteogenic differentiation (see Supporting Fig. 6).…”
Section: Mirna Signatures As Tools For Fracture Risk Assessment In Tymentioning
confidence: 99%
“…Moreover, under physiological conditions miRNA-31 was identified as a significant regulator of adult muscle and mesenchymal mammary progenitor stem cells and also is involved in diverse biological processes including fertility, embryonic development and bone formation (3)(4)(5). Interestingly, in neoplastic diseases miRNA-31 is either considered as a tumor-suppressor miRNA or oncogenic miRNA.…”
mentioning
confidence: 99%